First in-man studies demonstrate high prevalence of diabetes and cardiovascular disease in shift workers. (Research'eu results magazine)
Existing epidemiological studies have shown a correlation between shift working and a higher prevalence of type 2 diabetes and cardiovascular disease. The EURHYTHDIA project has developed predictive biomarkers and prevention strategies that should help identify and protect patients at risk.